Two cases of postherpetic Wolf's isotopic response - Zijia DAI; Ying WANG; Jiachen DOU; Yueting CUN; Guanglian YU; Zhenghui YANG; Tongyun LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Two cases of Wolf's isotopic response are reported here. Case 1: A 55-year-old female presented with pruritic erythema, papules on the site of healed herpes zoster on her right flank and abdomen for half a month. Combined with the histopathology, the diagnosis of eczema was made. Case 2: A 41-year-old male presented with pruritic erythema, papules on the left lumbar back, where remained pigmentation after treatment of herpes zoster for 20 days. Combined with the histological findings, the diagnosis of lichen planus was made.